In vitro antiviral effects of GS-441524 and itraconazole combination against feline infectious peritonitis virus. (May 2022) - Doki, Tomoyoshi; Takahashi, Ken; Hasegawa, Nobuhisa; Takano, Tomomi
Abstract: Feline infectious peritonitis virus (FIPV: virulent feline coronavirus) causes a fatal disease called feline infectious peritonitis (FIP) in wild and domestic cat species. Recent studies identified several antiviral drugs that are effective against FIPV. Drug combination is one of the important strategies in the development of novel treatments for viral infections. GS-441524, a nucleoside analog, and itraconazole, a triazole antifungal drug, have been reported that have antiviral effect against FIPV. This study aims to investigate whether the combination of GS-441524 and itraconazole has synergic antiviral effect against FIPV. The antiviral effect was measured by plaque reduction assay using felis catus whole fatus-4 cell. The plaque reduction of GS-441524 against type I FIPVs increased as the concentration of itraconazole increased. The similar result was obtained for type II FIPV. In addition, the calculated combination index (CI) demonstrated that there was a strong synergy between GS-441524 and itraconazole. It is concluded that the combination of GS-441524 and itraconazole may enhance the individual effect of each drug against replication of type I FIPVs and may contribute to development more effective treatment strategy for FIP. Highlights: The in vitro antiviral effect of combination of GS-441524 and itraconazole against FIPV. The plaque reduction of GS-441524 against FIPVs increased as the concentration of itraconazole increased. The calculated combination index demonstrated that there was a strong synergy between GS-441524 and itraconazole.